Toxicidade do Sistema Lagunar Piratininga-Itaipu (RJ) sobre o anfípodo bioindicador Tiburonella viscana - Rodes, Sofia Hart [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
A crescente urbanização nas regiões costeiras têm causado impactos nos ecossistemas aquáticos, incluindo a poluição química. Particularmente, as lagoas costeiras tropicais, ambientes prioritários para conservação, têm sido seriamente afetadas pela poluição urbana. O Sistema Lagunar Piratininga-Itaipu (Niterói, RJ), é um ambiente afetado por estressores antropogênicos resultantes de urbanização, enfrentando problemas como assoreamento e eutrofização, e, possivelmente, contaminação dos sedimentos. Nesse cenário, análises químicas são insuficientes para estimar a qualidade ambiental, pois não englobam os efeitos biológicos; com isso, a utilização de abordagens ecotoxicológicas é necessária para melhor avaliar o impacto da contaminação. Este estudo avaliou a toxicidade aguda dos sedimentos do Sistema Lagunar Piratininga-Itaipu sobre o anfípodo Tiburonella viscana. Foram realizados testes de toxicidade aguda de sedimento integral com amostras coletadas em 21 pontos, mais um sedimento controle (Ilhabela, SP), nos quais os anfípodos foram expostos durante 10 dias (10 org/réplica; 3 réplicas), sob condições controladas, seguindo o protocolo estabelecido pela ABNT. As sobrevivências dos anfipodos em cada amostra foram comparadas com o grupo controle utilizando o teste t’-student (p<0,05), permitindo classificar os sedimentos em não tóxicos ou tóxicos. No sistema lagunar, 65% dos sedimentos causaram toxicidade para T. viscana, com a região mais afetada sendo o Canal de Camboatá. Foi observada correlação da toxicidade com os níveis de Cu e Zn, o que sugere contribuição desses elementos ao efeito tóxico. Além disso, outros elementos ocorreram em concentrações elevadas, podendo ter contribuído com a toxicidade. A contaminação, resultante de uma complexa mistura de substâncias presentes nas lagoas, representa um risco à biota, e pode comprometer a integridade do sistema lagunar, ameaçando seus inúmeros serviços ecossistêmicos prestados.

Increasing urbanization in coastal regions has caused impacts on aquatic ecosystems, including chemical pollution. Particularly, tropical coastal lagoons, which represent priority environments for conservation, have been seriously affected by urban pollution. The Piratininga-Itaipu Lagoon System (Niterói, RJ), is an environment affected by anthropogenic stressors resulting from urbanization, facing problems such as siltation and eutrophication, and, possibly, sediment contamination. In this scenario, chemical analyses are insufficient to estimate environmental quality, as they do not encompass biological effects; therefore, the use of ecotoxicological approaches is necessary to provide an integrative overview of the ecological impacts of contamination. This study aims to evaluate the acute toxicity of sediments from the Piratininga-Itaipu lagoon system on the amphipod Tiburonella viscana, and determine, for some samples, the chemical groups involved with toxicity. Whole-sediment acute toxicity tests were performed with sediments collected at 21 sampling sites, plus a control sediment (Ilhabela, SP), in which the amphipods will be exposed for 10 days (10 org/replicate; 3 replicates), under controlled conditions, following the protocol established by ABNT. The survival of the amphipods in each sample will be compared with the control group using the Student t’-test (p<0.05), allowing the classification of the sediments as non-toxic or toxic. For T. viscana, 65% of sediments were toxic, with the most affected region being the Camboatá Canal. The contamination, resulting from a complex mixture of substances present in the lagoons, poses a risk to biota and may compromise the integrity of the lagoon system, threatening its numerous ecosystem services. In the lagoon system, 65% of sediments were toxic to T. viscana, with the most alarming region being the Camboatá Channel. A correlation between the toxicity and Cu and Zn levels was observed, suggesting that these elements contribute to the toxic effect. Moreover, other elements were present in high concentrations, which may have contributed to the toxicity. The contamination, resulting from a complex mixture of substances present in the coastal lagoons, poses a risk to the biota and may compromise the integrity of the lagoon system, threatening its numerous ecosystem services.
Toxicity of Sediments from the Piratininga-Itaipu Lagoon System (RJ) on the bioindicator amphipod Tiburonella viscana
Keywords: Toxicologia ambiental; Lagoas costeiras; Poluição marinha; Sedimentos estuarinos; Toxicidade Aguda; Acute Toxicity; Coastal Lagoons; Environmental toxicology; Marine Pollution; Estuarine sediments